HYDROCHEMICAL AND TOXICOLOGICAL CHARACTERIZATION OF AQUATIC ECOSYSTEM IN THE CHUSOVAYA RIVER WATER INTAKE FOR THE CITY OF PERM - Lapteva, A.K.; Shishkin, M.A.; Maslennikova, I.L. (Perm Federal Research Centre Journal, 2015)
Samples of river water and bottom mud near the head wall of the water intake were analyzed, as well as water at the stages of water treatment, backbone network at the pumping stations and at the terminal points of water consumption. The aim of the research was chemical-analytic and ecotoxicological evaluation of the contamination rate of water being supplied to the consumers from the Chusovaya river water intake. Determination of inorganic and organic pollutants, general toxicity and bacteriological parameters of initial and purified water was carried out.